Sanai’s political instructions in Hadiqat al Haqiqa and its sources - مریم مشرف (تاریخ ادبیات)
Sanai’s Hadiqah has manifested various tendencies of our moral and didactic literature. In this masnavi, along with inner education, which is the main goal and is manifested in the transmission of Sufi ethics, we witness a special type of political etiquette that has a source other than Sufi ethics, and it is political advice that has its roots in pre-Islamic literature. Political instructions create a didactic movement in Persian Masnavis. This movement was formed in Shahnameh and Gershasbnameh and some prose works such as al-Ghazali's Nasih al-Muluk and continued in Sanai’s Hadiqah. The political instructions in the Persian Masnavis are based on the axis of justice and encouraging the ruler to justice.